à propos de l’incroyance (xiiie-xvie siècle) - Jean-Pierre Albert (Les Dossiers du GRIHL)
Based on the example of Medieval Christianity, this paper deals with the possible existence of several kinds of criticism of religion (from atheism to irreligion and anticlericalism). Through a free reference to cognitive anthropology, it points out the vulnerability of religious ideas: critical views based on common sense or ways of thinking suspicion may be opposed to the unlikelihood of some faith truths, whose credibility is mostly based on the authority of the Church.